UNVEILING THE CHALLENGES FACED BY NON-PROFIT ORGANISATION IN MALAYSIA - Nur Hayati Ab Samad; Noor Hazlina Ahmad (International Journal of Accounting, Finance and Business, 2021)
Non-profit organisations (NPOs) play significant roles in social service deliveryand other aspects of sustainable development. In order to continuously fulfil theorganisational mission, the NPOs must address challenges that may hamper NPOssustainability. Hence, this study aimed to identify the challenges faced by NPOs to remainsustained. Through a semi-structured interview with NPOs in Malaysia, five mainchallenges outlined. NPOs faced difficulties in term of lack of fund, lack of human capitaland facilities, lack of cooperation and support from stakeholders, lack of trust, andmisalignment of interest between NPO and stakeholders. This study’s findings contributeto the literature of non-profit by highlighting the challenges faced by NPOs to remainsustained. This study’s findings help NPOs, and relevant regulators plan for the potentialremedy or strategies to tackle the identified challenges.